Pharmacokinetic Study of Atenolol in Rabbit Blood by Capillary Electrophoresis with Laser-induced Fluorescence Detection - Chen, Yuyun; Yang, Weiping (Asian Journal of Chemistry, 2011)
A sensitive method based on the use of capillary electrophoresis with laser-induced fluorescence (CE-LIF) detection was developed and validated for determination of atenolol in plasma of rabbit. Other components including a variety of amino acids and proteins in plasma did not interfere with the determination of atenolol under the experimental condition. The assay had a wide range (1.5-500 ng/mL) of linearity and a detection limit of 0.5 ng/mL. The intra- and interday precisions were satisfactory with relative standard deviation (RSD) less than 10 % and accuracy within 10 %. This method was successfully applied to pharmacokinetic study of atenolol in rabbit blood.